Raw physical properties measured on sediment core PS128_46-1 - Lester Lembke-Jene; Hinner Preckel; Andrea Catalina Gebhardt (PANGAEA, 2025)
Sound knowledge about the petrophysical characteristics of a sediment core is a prerequisite for any subsequent paleoenvironmental study relying on sediment proxies. Physical properties of whole-round sediment cores are acquired as a first step of sediment core description, prior to slicing of sediment cores into two halves. Here, we present raw physical-properties data of core PS128_46-1 acquired with a Geotek MSCL-S system on the unsplit core, retrieved during RV Polarstern expedition PS128 "EASI-1" from Nielsen Basin, Antarctica, in austral summer 2022.